Theology without walls: the transreligious imperative - Martin, Jerry L. (Routledge new critical thinking in religion, theology and biblical studies, 2020)
Paideias and programs for theology without walls / Robert Cummings Neville -- In spirit and truth : toward a theology without walls / Richard Oxenberg -- Revisiting Bellah's Sheila in a religiously pluralist century / Christopher Denny -- Theology without walls as open-field theology / Kurt Anders Richardson -- Theology without walls as the quest for interreligious wisdom / John J. Thatamanil -- My Buddha-nature and my Christ-nature / Paul Knitter -- Why not ten 60-foot wells? / Peter Savastano -- Theology without walls : an interspiritual approach / Rory Mcentee -- With open doors and windows : doing theology in the spirit of William James / Jonathan Weidenbaum -- Is theology without walls workable? : yes, no, maybe / Peter Feldmeier -- Daunting choices in transreligious theology : a case study / Wesley J. Wildman, Jerry L. Martin -- Cognitive science of religion and the nature of the divine : a pluralist, nonconfessional approach / Johan De Smedt, Helen De Cruz -- Love and desire, human and divine : a transreligious naturalist account / Wesley J. Wildman -- Dialogue and transreligious understanding : a hermeneutical approach / J. R. Hustwit -- Strategic religious participation in a shared religious landscape : a model for Westerners? / Paul Hedges -- How to think globally and affiliate locally / Jeanine Diller -- Theology without walls : is a theology for SBNRs possible? / Linda Mercadante -- More window than wall : the comparative expansion of confessional theology / S. Mark Heim -- Strong walls for an open faith / Francis X. Clooney, SJ -- A Hinduism without walls? : exploring the concept of the avatar interreligiously / Jeffery D. Long -- My path to a theology of Qi / Hyo-Dong Lee.